2008
DOI: 10.1039/b802973c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microchip capillary electrophoresis with external contactless conductivity detection for the determination of major inorganic ions and lithium in serum and urine samples

Abstract: The determination of inorganic ions in clinical samples in less than 90 seconds was demonstrated for microchip capillary electrophoresis using capacitively coupled contactless conductivity detection (C(4)D). Bare electrophoresis chips were used in combination with external electrodes which were part of the chip holder. In order to achieve the required selectivity and sensitivity, an optimization of the electrode layout was carried out. Limits of detection (LOD) of 1 microM for K(+), 1.5 microM for Ca(2+), 3 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 42 publications
2
41
3
Order By: Relevance
“…5, Na + and K + were baseline separated within 50 s and the resolution was 2.13. Theoretical plates for Na + and K + were 77 260 and 48 293 plates/ m, respectively, which are higher than those results reported in the literature, 8,16,[24][25][26] as shown in Table 1.…”
Section: Characteristics Of the Microchipcontrasting
confidence: 55%
See 4 more Smart Citations
“…5, Na + and K + were baseline separated within 50 s and the resolution was 2.13. Theoretical plates for Na + and K + were 77 260 and 48 293 plates/ m, respectively, which are higher than those results reported in the literature, 8,16,[24][25][26] as shown in Table 1.…”
Section: Characteristics Of the Microchipcontrasting
confidence: 55%
“…As expected, the LOD obtained by our chip is lower than those results obtained from chips with similar electrode geometry, thicker insulating layers and operated at low excitation frequencies, [24][25][26] as shown in Table 1. While it is higher than the results reported by Kubaň and Hauser,8,16,27 the excitation frequencies used in their work (500 kHz, 8 530 kHz, 16 600 kHz 27 ) are much higher than our applied frequency of 60 kHz and the range of the detector (0-300 kHz) used here, which is in line with the conclusion that the output of the detector increased sharply between 400 and 600 kHz. 13 Moreover, the LODs in their work were obtained when the optimized electrode geometry was used, and it has also been demonstrated that the electrode geometry had a significant effect on the sensitivity.…”
Section: Characteristics Of the Microchipcontrasting
confidence: 49%
See 3 more Smart Citations